Implementasi Pembelajaran Window Shopping Menggunakan Multimedia Untuk Meningkatkan Kemampuan Berbicara Siswa - Sariyah Astuti; Dian Puspita; Rara Marselina Jupon; Tri Yuni Hendrowati (Journal of Innovative and Creativity, 2025)
Speaking is an essential component when learning a language, especially when one is studying Indonesian. That capacity enables the students to express themselves ideas, perspectives, and information effectively in an organized and effective manner. In real life, however, a lot of children difficulty with communicating because they have things like a shortage of self-worth, limited knowledge, and an absence of possibilities for interaction in a learning environment that is interactive. The intention of this research project is to investigate and assess how using a multimedia-facilitated window-shop learning approach in Indonesian language instruction has benefited the communication skills of learners. The classroom-based Action Research (CAR) methods used in the present investigation comprises two phases of actions containing four stages each of them: preparation, implementation, observing, and analysis. qualitative questionnaires, evaluation, and document were used for gathering findings from the study. Based to the study's conclusion, the students' assessments improved dramatically as they discovered how to exchange information via multimedia-facilitated window shopping.